Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan pada PT Siantar Top Tbk Cabang Bekasi - Nur Fitriany, Neisa; Wulansari, Retno (Jurnal Disrupsi Bisnis, 2024)
The purpose of this study was to determine the effect of work environment and work stress on employee performance at PT. Siantar Top Tbk Bekasi branch. The method used quantitative. The sampling technique used saturated sampling and obtained a sample of 60 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. Based on the results of this study, it was known: (1) The work environment has a significant effect on employee performance with the regression equation Y = 18.308 + 0.540X1 hypothesis test obtained t calculate >t table or (6.829>2.002) thus Ho rejected H1 accepted means that there was a significant influence of the work environment on employee performance. (2) work stress has a significant effect on employee performance with a regression equation of 46,300 + 0.218X2 hypothesis test obtained t count>t table or (4.704>2.002) thus H0 rejected H1 accepted means that there was a significant effect of work stress on employee performance. (3) Work environment and work stress simultaneously have a significant effect on employee performance with regression equation Y = 27.053 + 0.459X1 + 0.155X2 with autocorrelation value 2.108, correlation coefficient value 0.758, adjust R square determination coefficient value was 0.574 or 57.4% while the rest (100% - 57.4% = 42.6%) is influenced by other factors. Based on the results of the F test, it was known that the value of F count is 38,479 where F count was greater than F table or by 38,479 > 2,770), then H0 rejected Ha accepted, meaning that the work environment and work stress have a positive and significant effect on employee performance. Keywords: Work Environment, Work Stress, Employee Performance